1986
DOI: 10.1128/iai.52.3.725-729.1986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymyxin B and colimycin on induction of plasminogen antiactivator by lipopolysaccharide in human endothelial cell culture

Abstract: The effect of lipopolysaccharide (LPS) on the production of fibrinolytic inhibitor by human endothelial cells was determined because results of previous experiments have shown us that it is possible to stimulate this synthesis with muramyl dipeptide. Treatment of these cells with LPS resulted in a marked enhancement of fibrinolytic inhibitor, as estimated in a urokinase-induced fibrinolysis assay. A dose-response curve was obtained for LPS concentrations ranging from 10 to 1,000 ng/ml, thus demonstrating the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It is not yet established whether this in vivo effect of endotoxin is direct or indirect via the induction of TNF and/or interleukin 1 (24). The latter two compounds, as well as endotoxin, stimulate PAI-1 release and downregulate t-PA release by endothelial cells (25)(26)(27)(28)(29)(30) and fibrosarcoma cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet established whether this in vivo effect of endotoxin is direct or indirect via the induction of TNF and/or interleukin 1 (24). The latter two compounds, as well as endotoxin, stimulate PAI-1 release and downregulate t-PA release by endothelial cells (25)(26)(27)(28)(29)(30) and fibrosarcoma cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…To understand the mechanisms underlying LPS-induced signals in the first 30 min, i.e., before the addition of CHX, we first examined the effects of polymyxin B, TPCK, genistein, herbimycin A, PD98059, SB202190, and SB203580 on the cytotoxicity induced by LPS and CHX. Polymyxin B [29] and TPCK [30] have been reported to inhibit LPS-induced signals, genistein and herbimycin A are inhibitors of tyrosine kinases [31,32], PD98059 is a MEK inhibitor [33], and SB202190 and SB203580 are MAP kinase inhibitors [34][35][36]. As shown in Figure 5a, the release of LDH induced by LPS and CHX was inhibited by the addition of polymyxin B, TPCK, genistein, or herbimycin A, but not by PD98059, SB202190, or SB203580 (Fig.…”
Section: Lps-induced Signals Activate the Caspase-3-like Protease In mentioning
confidence: 99%
“…It has been shown that the release of PAI is drastically increased after stimulation with endotoxin. 303 " 307 This inhibitor is active against t-PA as well as u-PA. 304,305 Dosne and colleagues 308 were the first to describe the production of a fibrinolytic inhibitor by cultured endothelial cells derived from human umbilical vein.…”
Section: Effects Of Endotoxin On Fibrinolytic Activitiesmentioning
confidence: 99%